The additive manufacturing of model polymer nanolaminates via automated spray deposition - Dunkerley, Erik (2018)
Polymer nanocomposites represent a key addition to the palette of advanced polymeric materials available to us in the context of additive manufacturing. However, our understanding of their properties, and thus our ability to predict them and to design parts based on them, remains limited. With this in mind, nanolaminates have been formed via an additive process developed in our group and referred to as automated spray deposition; these materials have been characterized with the express purpose of better understanding the composition-structure-properties relations critical to our ability to create high performance polymeric materials by design via additive techniques. Here we present a preliminary comparison of the dynamic mechanical properties of two families of nanolaminates, essentially identical except for the polarity of the polymer phase and the strength of polymer / nanofiller interactions, with the aim of better understanding the mechanical response of such materials.